Proceso De Atención De Enfermería en adulto mayor con traumatismo intracraneal - Mendoza Garofalo, Jessica Lorena (2018)
This clinical case deals with an intracranial trauma that is all that energy or force that acts on the head and its continent, with that originates the anatomical lesions and functional alterations, being a very high incidence of morbidity and mortality, taking into account the causes more frequent are the falls and accidents of transits. The most common causes of traumatic brain injuries are: Traffic accidents, represents approximately 45% of injuries, speeding and alcohol consumption are two elements to bear in mind in the consequences and assessments of traumatic brain injury. Sports accidents, injuries caused by accidents in football, boxing, baseball, hockey, etc. Falls, represents 33% of mild head injuries, subdural hematomas or cerebral contusion, aggressions, represents 2.6% of TBI, includes fractures of facial bones and / or facial contusions. The symptoms of a traumatic brain injury will vary in relation to the size of the lesion and the structure of the affected brain, bleeding of the scalp, superficial hematoma of the scalp, development of blood clots, fracture of the skull with possible collapse of bony areas. , laceration of brain tissue, headache, nausea, vomiting, fatigue, drowsiness or fatigue. To determine the appropriate treatment for traumatic brain injury this will depend on the severity of this, the different activities will be from a relative rest in bed, to cures in health unit, medications, surgical intervention and physical and psychological rehabilitation. In mild cranioencephalic traumas, part of their treatment is bed rest plus administration of analgesic medication. In cerebral lesions of moderate or severe origin, it is necessary to ensure sufficient cerebral oxygenation, as well as to maintain hemodynamics and avoid movements in the head and neck. It is possible, depending on the patient's condition, to administer drugs to limit secondary damage, such as: diuretics, anticonvulsant drugs, and coma-inducing drugs. Finally, there may be very complex cases in which surgical intervention is required, such as: Extraction of bruises, craniotomies, repair of fractures of the skull.